Shariah and alcohol issue - Baharum, Nur Bahirah; Awang, Mohd Daud; Arshad, Syariena; Abd Gani, Siti Salwa (Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2020)
Alcohol is an organic solvent that generally used in research and industry especially in food, pharmaceutical and beverage products. It is also reported to be widely used in cosmetic industries to produce cosmetic products such as perfume, skin care and personal care products. However, the discussions on shariah and alcohol issue are still very limited. Thus, the main focus of the present study is to analyze the status of alcohol in shariah by focusing on analyzing the history of alcohol. Furthermore, issues related to alcohol in Islam are also discussed in this article.